(untitled) (International Journal of Engineering Materials and Manufacture, 2017)
Natural fiber such as kenaf, sisal, pineapple leaf and banana are growing popular nowadays due to its favor over traditional glass fiber and inorganic material. It is a renewable resources and abundantly available in the market. The composites made of natural fiber are economical, lightweight and environmental friendly. This study works on producing a composite based on the Banana fiber reinforced epoxy resin by using the method of Vacuum Infusion and Hand Lay-up. Banana fiber will be treated with Sodium Hydroxide (NaOH) and water solution for 1 hour and then dried in the oven for 24 hours at 100Â°C. The composite will be produce based on different fiber volume fraction of 20% and 40% as well as different fiber length of 127mm, and 63mm. In Vacuum Infusion process, a mold made of aluminium have been manufactured according to the size of specimens of 127mm x 12.7mm x 3.2mm in dimension will be used in the preparation of specimens. The specimens of different volume fraction and fiber length produced by vacuum infusion and hand lay-up method will be mechanically tested through flexural test. The highest flexural strength is the specimen made by vacuum infusion process with 40% volume fraction and 63mm fiber length, which is 136.27MPa while for the hand lay-up process, the highest flexural strength is 80.71 with 40% volume fraction and 63mm fiber length.